Establishing the Legal Force of Land Technical Considerations in Indonesia’s Spatial Planning through a Normative Analysis of ATR BPN Regulation No. 12 of 2021 - Helmi Tri Pamungkas (Lambung Mangkurat Law Journal, 2025)
In Indonesia, the central land issue lies in inequality, where a small segment of the population controls vast tracts of land while the majority must survive on limited plots. This condition highlights the urgency of a land legal system that is adaptive, equitable, and responsive to social change. The Land Technical Consideration (Pertimbangan Teknis Pertanahan/PTP), as regulated under the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Regulation No. 12 of 2021, plays a pivotal role as a legal instrument for land use control and sustainable spatial governance. This research employs a normative legal research method focusing on the analysis of legal provisions to identify underlying legal principles, standards, and dogmas. The study examines how PTP contributes to ensuring consistent, equitable, and sustainable land ownership, control, utilization, and management. Findings demonstrate that PTP functions not only as a procedural requirement but also as a substantive tool to align land allocation with spatial planning objectives, considering aspects such as authority, ownership status, competency, adequacy, and land-related challenges. By situating PTP within the broader framework of sustainable spatial planning governance, this research underscores its implications for improving land equity and reinforcing legal certainty in Indonesia’s land management system.